2013
DOI: 10.1038/npp.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clock in Ethanol-Related Behaviors

Abstract: Mice with a mutation in the Clock gene (ClockD19) exhibit increased preference for stimulant rewards and sucrose. They also have an increase in dopaminergic activity in the ventral tegmental area (VTA) and a general increase in glutamatergic tone that might underlie these behaviors. However, it is unclear if their phenotype would extend to a very different class of drug (ethanol), and if so, whether these systems might be involved in their response. Continuous access voluntary ethanol intake was evaluated in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 62 publications
(85 reference statements)
2
85
0
Order By: Relevance
“…Moreover, when we measured cocaine-induced CPP, we found that NAc infected AAV- Clock shRNA injected mice were indistinguishable from Scramble injected mice at doses in which there is an increase in preference in the Clock mutant mice (16) (Figure 3C). This is in contrast to the hyperactivity and increased alcohol preference which is observed when Clock expression is reduced specifically in the VTA (19, 35). Thus, a knock-down of NPAS2, but not CLOCK in the NAc is sufficient for decreased cocaine preference.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, when we measured cocaine-induced CPP, we found that NAc infected AAV- Clock shRNA injected mice were indistinguishable from Scramble injected mice at doses in which there is an increase in preference in the Clock mutant mice (16) (Figure 3C). This is in contrast to the hyperactivity and increased alcohol preference which is observed when Clock expression is reduced specifically in the VTA (19, 35). Thus, a knock-down of NPAS2, but not CLOCK in the NAc is sufficient for decreased cocaine preference.…”
Section: Resultsmentioning
confidence: 69%
“…Although Clock is also expressed in the NAc, it does not appear to have a prominent role in the regulation of cocaine reward in this region. Previous studies have established that CLOCKs actions in the ventral tegmental area (VTA) are important for the regulation of dopaminergic activity, as well as mood, anxiety and reward-related behavior (19, 22, 35). Thus, we propose that Clock regulates drug reward primarily through its actions in the VTA, while NPAS2 primarily acts in the NAc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of the Clock gene in the mouse VTA leads to increased alcohol intake (Ozburn et al, 2013), and mice lacking the circadian rhythm gene Period 1 (Per1) exhibit augmented alcohol intake following a social-defeat stressor as compared with WT mice (Dong et al, 2011). However, this signaling pathway seems to be more complex as the inhibition of casein-kinase-I-epsilon/delta (CKI ε/δ), which plays a role in the circadian system, decreases alcohol consumption in an alcohol-deprivation paradigm (Perreau-Lenz et al, 2012).…”
Section: Protective Signaling Pathwaysmentioning
confidence: 99%
“…Results of this study indicate that the most differentially expressed genes in the NAc were involved in circadian rhythms (55). Recently, we found that chronic alcohol consumption (in a two bottle choice paradigm) and abstinence resulted in decreased Clock expression in the NAc and VTA (56). Moreover, Chen et al (2004) (57) found that chronic ethanol intake via liquid diet shifted Per1 and Per2 gene expression rhythms in the arcuate nucleus (an area that sends projections to the NAc).…”
Section: Introductionmentioning
confidence: 99%